ANALYSIS OF SALIVARY COMPONENTS TO EVALUATE THE PATHOGENESIS OF AUTISM IN CHILDREN - Arumugam, Geetha; Sridharan, Sujatha (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Autism is a neurodevelopmental disorder affecting the cognitive and social skills with severe implications on the affected individual's ability to lead productive and independent life. The present study is focused on evaluating the alteration in the levels of salivary components including antioxidants, in children with different grades of severity of autism. Materials and Methods: Unstimulated whole saliva sample was collected from normal, and autistic children grouped as medium functioning autism (MFA) and low functioning autism (LFA) based on childhood autism rating scale score (n-20 in each group). Concentration of protein, cholesterol, thiocyanate (SCN¯), mucin, uric acid, lipid peroxides (LPO), reduced glutathione (GSH), α-amylase and antioxidant enzymes activity were determined in saliva. Results: LFA group showed elevated levels (p=0.000) of protein, SCN¯, mucin, uric acid, α-amylase and LPO when compared to MFA group and normal children. Antioxidant enzymes, cholesterol and GSH levels were significantly decreased (p=0.000) in LFA than in MFA and normal children. Significant elevation in the levels of SCN¯ (p=0.001) and mucin (p=0.004) was observed in LFA than in MFA. The electrophoretic pattern revealed that protein corresponding to 52-63 kD are significantly elevated, and 63-76 kD are decreased in autistic children. Western blot of salivary glutathione-Stransferase- 2 (GST-2) showed decreased activity in LFA than in MFA and normal children. Conclusion: The results showed that alteration in salivary components, including antioxidant enzymes, especially GST was proportional to the severity of autism, which can act as biological marker for diagnosing autism and also saliva can be considered as a non-invasive specimen to study the pathogenesis of autism like other biological specimen. Keywords: Antioxidants, Autism, Glutathione-2, Low functioning autism, Medium functioning autism, Protein marker, Unstimulated saliva